Geography-Based Study Module Development Environment in East Lombok - Santriani, Esis (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This article is written to (1) study the development of module-based geographic environment in East Lombok (2) know the quality of the environment based on the geography module material lithosphere dynamics and their impact on life (3) knowing barriers in developing environment-based geography module in East Lombok. This type of research is quantitative descriptive. Quality geography module seen from the level of validity that includes feasibility aspects of content, presentation, graphics, language and environment-based. Validity of data obtained through the study of geography modules and expressed with values normalized gain score. The study found that the development of geography module developed by a team MGMPs eastern Lombok. The quality of the environment based on geography module seen from the aspect of the content of 79% feasibility, feasibility aspects of presentation of 69.6%, 85% and the feasibility language environment based 81.25%.